Lower socioeconomic status associated with higher tuberculosis rate in South Korea - Seong-Woo Choi; Jeong-Ja Im; Sang-Eun Yoon; Seo-Hee Kim; Jun-Hwi Cho; So-Jung Jeong; Kyung-Ae Park; Young-Sung Moon (BMC Pulmonary Medicine, 2023)
Abstract Background Tuberculosis is an infectious disease influenced by social factors rather than a simple infectious disease. In this study, we investigated the relationship between tuberculosis rates and socioeconomic status. Methods This study was conducted using data of the 49,483 participants of the Korean National Health and Nutrition Examination Survey (KNHANES) VI–VIII (2013–2021). The relationships between tuberculosis rates and the quartiles of monthly household income and education level were examined using a multivariate logistic regression analysis. Results The KNHANES data revealed that the prevalence of tuberculosis as substantially related to monthly household income (odds ratio [OR], 6.0; 95% confidence interval [CI], 1.1–32.0 for lowest vs. highest incomes) and education level (OR, 3.8; 95% CI, 1.2–12.0 for 10–12 years vs. ≥13 years; OR, 4.1; 95% CI, 1.2–14.8 for ≤ 6 years vs. ≥13 years). Furthermore, current tuberculosis treatment was significantly related to monthly household income and education level. Conclusion There were substantial correlations between tuberculosis rates and socioeconomic status in South Korea.